2023
DOI: 10.3390/ijms25010340
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Bevacizumab and the Risk of Chronic Kidney Disease Development in Taiwan Residents: A Population-Based Retrospective Cohort Study

Lon-Fye Lye,
Ruey-Hwang Chou,
Tsai-Kun Wu
et al.

Abstract: Vascular endothelial growth factor (VEGF) plays a significant role as a pro-angiogenic and pro-permeability factor within the kidney. Bevacizumab is a pharmaceutical monoclonal anti-VEGF antibody that inhibits the growth of new blood vessels, which blocks blood supply and thereby restricts tumor growth. Thus, we conducted a nationwide study to explore the risk of chronic kidney disease (CKD) development in Taiwan residents after bevacizumab therapy. We drew data from the extensive National Health Insurance Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Bevacizumab, a recombinant human monoclonal antibody that binds to all known vascular endothelial growth factor A (VEGF-A) subtypes and exerts antiangiogenic effects by blocking the binding of VEGF-A to VEGF receptors (primarily VEGFR-1 and VEGFR-2) on the surface of endothelial cells, as VEGF-A binds to VEGFR-1 and VEGFR-2 to promote endothelial cell proliferation, activate survival pathways, and form new blood vessels. Therefore, bevacizumab plays an important role in the treatment of advanced cancer, including NSCLC ( 109 , 110 ). The most common renal impairment of bevacizumab is proteinuria in clinical practice ( 111 ).…”
Section: Vegf Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bevacizumab, a recombinant human monoclonal antibody that binds to all known vascular endothelial growth factor A (VEGF-A) subtypes and exerts antiangiogenic effects by blocking the binding of VEGF-A to VEGF receptors (primarily VEGFR-1 and VEGFR-2) on the surface of endothelial cells, as VEGF-A binds to VEGFR-1 and VEGFR-2 to promote endothelial cell proliferation, activate survival pathways, and form new blood vessels. Therefore, bevacizumab plays an important role in the treatment of advanced cancer, including NSCLC ( 109 , 110 ). The most common renal impairment of bevacizumab is proteinuria in clinical practice ( 111 ).…”
Section: Vegf Inhibitorsmentioning
confidence: 99%
“…Zhu et al ( 107 ) have shown that the incidence of all-grade hypertension was 21% and a significantly higher incidence in patients with renal cell carcinoma in a meta-analysis of total 4609 patients treated with sunitinib. In the treatment of lung cancer, bevacizumab is more likely to induce nephrotoxicity than other VEGF inhibitors ( 108 , 109 ).…”
Section: Vegf Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation